A randomized controlled trial of a Group psychological intervention to increase locus of control for alcohol consumption among Alcohol‐Misusing Short‐term (male) Prisoners (GASP). (13th March 2020) - Taylor, Pamela J.; Playle, Rebecca; Robling, Michael; Bezeczky, Zoe; John‐Evans, Hannah; Dimitropoulou, Polyxeni; McNamara, Rachel; Moriarty, Yvonne; Summers, Zelda; Bagshaw, Ruth
Abstract: Background and aim: Reducing alcohol misuse by male prisoners is an important global issue. Control of drinking behaviour could be a useful target for intervention in this population, and locus of control could be a causal factor in this. We aimed to assess the effect of a clinical psychologist‐facilitated group intervention on male prisoners' locus of control of drinking behaviour. Design: A two‐arm, single‐site, open, randomized controlled trial. Setting: A category B local training prison in South Wales, housing about 770 mainly sentenced men. Participants: Prisoners serving less than 2 years who met inclusion criteria for pre‐imprisonment alcohol misuse, alone or with drug misuse. A total of 119 were allocated to the intervention arm and 119 to the control arm; 104 and 87, respectively, completed the post‐randomization baseline interview and 68 and 60 completed a second interview approximately 4 weeks later, respectively, after intervention or treatment as usual (TAU) alone. Intervention: Nine clinical psychologist‐facilitated groups in the prison over 3 weeks. Range of participants per session was one to seven, with three to five most usual. Measures: The primary outcome was locus of control of behaviour (LCB); secondary outcomes included mental state generally (comprehensive psychiatric rating scale/CPRS) and specifically (Beck Depression Inventory/BDI). An integral process evaluation was conducted. Findings: LCB scores decreased during the study, but without significant intervention effect [−1.7, 95% confidence interval (CI) = –5.1 to 1.6, P  = 0.329]. Change among completers in the control group was from a mean score of 37.4 [standard deviation (SD) = 10.0] to 33.7[SD = 11.7] and in the intervention group from 37.4 (SD = 11.6) to 31.9 (SD = 11.8). Secondary outcomes, including change in mental state, did not differ between arms, but 686 (64%) sessions were lost, most because of 'prison issues'. Conclusions: A clinical psychologist‐facilitated group intervention did not have a statistically significant effect on sense of control of drinking behaviour among men with pre‐imprisonment alcohol misuse serving less than 2 years in a South Wales prison. The study proved coterminous, however, with 40% prison staff cuts which seem likely to have contributed to the high loss of group sessions and possibly overwhelmed any treatment effect. Intervention completion failures, previously cited as harmful, had no effect here, so the trial should be repeated when the prison climate improves.